Desenvolvimento e validação de um modelo matemático para o cálculo da área superficial de frangos de corte - Silva, Eberson (2007)
The surface area (As) of poultry is an important parameter in heat and mass transfer calculation, being that its determination using non-destructive methodologies, as moiré technique (TM), allows the automation of As determination that results in accuracy and speed gains, besides the maintenance of the object integrity. However, it was aimed with the present work to develop and to validate an empirical model to estimate the broiler chicken’s surface area through a conventional and image analysis method. Eighty four Ross broiler chickens were used in this research, thirty seven male and forty seven female, with body masses covering all growing phase. In the laboratory, each randomly selected chicken had its dimensions (length, width and height) and body mass evaluated. Following, the chicken was illuminated with a source of light, in which the fringes were projected, the image captured, and processed to obtain the object shape by TM. Finally, the chicken skin with feathers was taken off to determine As used as reference for TM calibration and validation. Part of test results was used to fit the As equation and to calibrate the TM and part was used to validate both. Results showed that the empirical equation to determine As is statically significant (P<0.0001) and presents a coefficient of determination of 0.9886, being subsequently validated via t test (P>0.05). TM and image analysis were as adequated for broiler chicken three-dimensional shape recovery and As determination, showing as an adequated non-invasive and non –destructive biometric technique.